2019
DOI: 10.1021/acs.organomet.9b00442
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Mechanisms of Di-tert-butylaminoarsane (DTBAA)

Abstract: III−V semiconductors containing small amounts of nitrogen ("dilute nitrides") are very promising material systems for optoelectronic applications. Devices based on dilute nitrides currently suffer from problematic C incorporation. To overcome this problem, a novel nitrogen (N) and arsenic (As) precursor for metal−organic vapor phase epitaxy (MOVPE) of the dilute nitride di-tertbutylaminoarsane (DTBAA) has been introduced. DTBAA in comparison to the commonly used 1,1-dimethylhydrazine (UDMHy) showed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…[22] Recently, we showed that interpnictogen compounds are useful as precursors for the preparation of doped semiconductors via MOCVD processes. [27][28][29][30][31] Using aryl substituents at bismuth, could give access to interpnictogen compounds that prove useful as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Recently, we showed that interpnictogen compounds are useful as precursors for the preparation of doped semiconductors via MOCVD processes. [27][28][29][30][31] Using aryl substituents at bismuth, could give access to interpnictogen compounds that prove useful as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…These reaction pathways have been predicted by density functional theory calculations for the As analogue DTBAA and are on the one hand shown in decomposition studies of this precursor. On the other hand these pathways are also known for other metal–organic precursors with tert -butyl groups such as TBAs. ,, Another expected reaction pathway of the tert -butyl groups is decomposition through β-H elimination. In this case a H atom at one of the C atoms in a β position within the tert -butyl group interacts with the p orbitals of the phosphorus atom of the same molecule.…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, NH 3 was detected with the same intensity as that for DTBAP. The detected NH 3 is attributed to the formation of aminyl radicals (NH 2 • 16 u) during the decomposition of DTBAP and was also observed as a decomposition product of DTBAA . This indicates a radical decomposition of the N–P bond of the molecule, which leads to the formation of NH 2 • and DTBP • (145 u).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations